Bimanual movement control: insights from golf ball striking - Tinmark, F. (2014)
The aim of this thesis was to gain insight into the control of complex bimanual movements that are both fast and accurate. For this, skilled golf ball striking was used as a model in two experimental studies (I and III). The thesis also includes two methodological studies (II and IV), intended to assist in present and future investigation on bimanual movement control. Study I shows a common kinematic proximal-to-distal sequencing (PDS) pattern and speed-summation effect in skilled golf players of both genders. Using a common PDS movement strategy in golf ball striking at various endpoint speeds appears beneficial from mechanical and control points of view and could serve the purpose of providing both high speed and accuracy. In Study II a general expression for mobility was derived, which can be applied for extending the theory of mobility to double-handed grasping and manipulation. Study III found that kinematic contributions to endpoint velocity at slow, medium and fast test conditions were provided by the same subset of possible joint rotations. However, the specific subset differed between levels of expertise. The inertial behavior of the linkage arms-hands-club promoted movement parallel to and resisted movement orthogonal to the club path close to ball impact, at all endpoint speeds investigated. These findings extend previous knowledge regarding endpoint control in single-limb movements. Moreover, results regarding movement organization in Study I together with results in Study III regarding inertial behavior suggest the existence of limb configurations able to simultaneously exploit intersegmental dynamics and endpoint mobility in a proficient manner. To make the control of intersegmental dynamics in bimanual striking transparent, however, torques originating from segmental in teractions should be determined. However, when hands are placed next to each other or are overlapping it becomes challenging to find placements for standard force sensors which allow separation of right and left hand forces without altering normal behavior. As partially explored in Study IV, pressure mapping of the right hand together with inverse dynamics calculations for the golf club can potentially provide an adequate solution.